Optically responsive supramolecular polymer glasses - Diederik W. R. Balkenende (Nature Portfolio, 2016)
The ability to heal whilst maintaining original functionality is important for establishing materials with superior longevity. Here, the authors demonstrate a supramolecular polymeric coating which exhibits excellent optical and mechanical properties, even following damage repair.